Testing dynamic consistency and consequentialism under ambiguity - Bleichrodt, Han; Eichberger, Jürgen; Grant, Simon; Kelsey, David; Li, Chen (CEDEX discussion paper series, 2020)
Accounting for ambiguity aversion in dynamic decisions generally implies that either dynamic consistency or consequentialism must be given up. To gain insight into which of these principles better describes people's preferences we tested them using a variation of Ellsberg's three-color urn experiment. Subjects were asked to make a choice both before and after they received a signal. We found that most ambiguity neutral subjects satisfied both dynamic consistency and consequentialism and behaved consistent with subjective expected utility with Bayesian updating. The majority of ambiguity averse subjects violated at least one of the principles and they were more likely to satisfy consequentialism than dynamic consistency.
Keywords: Graue Literatur